2002
DOI: 10.1073/pnas.102291599
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Gα 12 with Gα 13 and Gα q signaling pathways

Abstract: The G12 subfamily of heterotrimeric G-proteins consists of two members, G 12 and G13. Gene-targeting studies have revealed a role for G 13 in blood vessel development. Mice lacking the ␣ subunit of G 13 die around embryonic day 10 as the result of an angiogenic defect. On the other hand, the physiological role of G12 is still unclear. To address this issue, we generated G␣ 12-deficient mice. In contrast to the G␣ 13-deficient mice, G␣12-deficient mice are viable, fertile, and do not show apparent abnormalities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 57 publications
6
127
0
Order By: Relevance
“…Embryos carrying one G␣12 allele with G␣13 null survived until E9, whereas those that had one G␣12 and one G␣13 alleles were viable. These genetic studies revealed that both an overlapping and a distinct function of G␣12-and G␣13-mediated signaling exists in mouse embryonic development (8,29). The G␣12-RhoGEF-Rho pathway in C. elegans is also critical in embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Embryos carrying one G␣12 allele with G␣13 null survived until E9, whereas those that had one G␣12 and one G␣13 alleles were viable. These genetic studies revealed that both an overlapping and a distinct function of G␣12-and G␣13-mediated signaling exists in mouse embryonic development (8,29). The G␣12-RhoGEF-Rho pathway in C. elegans is also critical in embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking Gα 13 , the α-subunit of G 13 , die in utero because of a defect in angiogenesis, whereas Gα 12 -deficient mice are phenotypically normal 10,11 . To circumvent embryonic lethality of mice deficient in Gα 13 and to study the role of Gα 12 -and Gα 13 -mediated signaling in platelet activation, we used Cre/loxP-mediated recombination to conditionally inactivate Gna13, the gene encoding Gα 13 , alone or in a Gα 12 -deficient (Gna12 -/-) background.…”
mentioning
confidence: 99%
“…In G␣ 12 G␣ 13 knock-out MEF cells, neither G protein-coupled receptors for thrombin or lysophosphatidic acid nor receptor tyrosine kinases for PDGF or epidermal growth factor induced migration of these cells (18,19,23). To visualize directly the effect of G␣ 12 and G␣ 13 on actin cytoskeletal reorganization, we utilized live cell imaging techniques to compare the dynamics of actin cytoskeletal reorganization in wild-type and G␣ 12 G␣ 13 knock-out MEF cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Culture and Transfection-G␣ 12 Ϫ/Ϫ G␣ 13 Ϫ/Ϫ MEF cells were provided by J. Gu and M. Simon (California Institute of Technology) and have been previously described (18,19). Cells were grown in DMEM containing 10% fetal bovine serum and penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation